Pengaruh Kualitas Pesan Kampanye #BerkainGembira terhadap Sikap Generasi Z Pada Penggunaan Kain Tradisional - Skolastika Damara Putri Beda (Universitas Muhammadiyah Jember, 2022)
Traditional cloth is currently in a state of concern due to a lack of buying interest, which impacts many traditional cloth industries going out of business. On the other hand, many young people in Indonesia are not familiar with various types of traditional fabrics typical of the archipelago. This paper discusses the quality of the #BerkainGembira campaign message on the attitude of Generation Z Instagram Followers @swaraharga on the use of traditional cloth. This study uses a survey method with a questionnaire instrument. It uses a non-random sampling technique, namely purposive sampling with the criteria for followers of the Instagram account @swarahasil who belong to Generation Z, namely those born in 1995-2009 or aged 12 to 26 years with a total of 100 samples. The results showed that there was a strong relationship between the quality of the campaign message #BerkainGembira) and the attitude of Generation Z Instagram followers @swaraharga. The quality of the message of the #BerkainGembira Campaign, which includes aspects of message content and message structure, has an influence of 61.2% on Generation Z Instagram Followers @swaraharga, namely on the cognitive, affective, and conative aspects.